Analysis of the risk of diabetes mellitus type 2 in women workers at a reference hospital in Asuncion, Paraguay - Sosa, María Luisa; Jara, Cynthia Mireya; Pratt, Paola; Quintana, María Elida; García-Salinas, Héctor (Medicina Clínica y Social, 2024)
Introduction: Obesity, age, sedentary lifestyle, and family history of diabetes mellitus are risk factors for type 2 diabetes mellitus (T2DM). Objective: determine the probable risk of developing T2DM in the next 10 years in working women at a reference hospital in Asunción, Paraguay. Methodology: This cross-sectional observational descriptive study was conducted with physicians, nurses, and administrative staff. Data were collected over three months using the FINDRISK test to assess diabetes risk, which consists of eight questions about age, body mass index, waist circumference, physical activity, fruit and vegetable consumption, history of blood pressure, high blood pressure and high glucose, and diabetes diagnosed in family members. Descriptive statistics in the form of frequencies and percentages, as well as analytical statistics using the Mann-Whitney and Kruskal-Wallis tests, were used to analyze the data. Results: A total of 112 women participated in the study, with more than 40% in the age range of 31–40 years. The waist circumference of 80-88 cm was the most common (38.4%). It was found that 33% of participants were overweight. Almost 60% of the participants did not perform daily physical activities. More than 38% of the first-degree relatives had a history of diabetes.  Of the surveyed participants, 67.9%had some risk of developing T2DM in the next 10 years and 22 had a high or very high risk according to the FINDRISK test. Participants aged 35 years had a significantly higher risk (p=0.008). Conclusion: A high prevalence of overweight and obesity was observed, with 67.9% of the respondents showing some degree of risk for developing T2DM in the next 10 years, of which nearly 20% were categorized as high or very high risk.
Keywords: diabetes mellitus; risk factor; Health promotion; obesity; chronic non-communicable disease